American Urological Association, American College of Emergency Physicians and American College of Radiology Quality Improvement Summit 2017: Challenges and Opportunities for Stewardship of Urological Imaging. Issue 5 (September 2019) - Nielsen, Matthew E.; Averch, Timothy; Chi, Thomas; Fredricks, Nancy; Shiu-Kai Fung, George; Montie, James; Purysko, Andrei; Remer, Erick M.; Smith-Bindman, Rebecca; Sternberg, Kevan; Venkatesh, Arjun; Wolf, J. Stuart; et al.
Abstract: Introduction: Since 2014 the AUA (American Urological Association) has convened several Quality Improvement Summits to provide education and promote dialogue around issues of quality improvement and patient safety. The 2017 Summit, Challenges and Opportunities for Stewardship of Urological Imaging, organized in partnership with the American College of Radiology and the American College of Emergency Physicians, highlighted opportunities for collaborative improvement in the value, safety and quality of imaging for patients with urological conditions. Methods: The Summit was held at AUA headquarters in Linthicum, Maryland on October 21, 2017. Each talk, panel and working group held during the summit highlighted gaps in care being addressed by physician led stewardship initiatives in imaging, in general, as well as multiple specific examples related to prostate cancer and urinary stone disease. Results: Presentations facilitated information exchange on quality efforts between clinicians across disciplines and care settings and served to educate urology practitioners, primary care physicians, and specialists about existing patient centered quality improvement programs. Conclusions: This exchange serves to accelerate adoption of evidence-based practices and brings together stakeholder organizations to form partnerships that facilitate the further development of research and policy agendas to advance physician led stewardship of advanced imaging across emergency medicine, radiology and urology. In parallel, this meeting established a consortium to develop and disseminate tools for facilitating organizational improvement activities needed to enhance the quality and safety of medical care.